A TEST OF ANALYTICAL THINKING AND CHEMICAL REPRESENTATION ABILITY ON 'RATE OF REACTION' TOPIC - Antuni Wiyarsi; Atina Rizanatul Fachriyah; Didi Supriadi; Muhd Ibrahim bin Muhamad Damanhuri (LPMPP Universitas Negeri Yogyakarta, 2019)
Assessments play an important role in chemistry learning and for specific uses. The construction of a test based on multiple representation approaches is needed for measuring the 21st century thinking skills. This study aims to construct and validate a standardized test to measure students’ analytical thinking and chemical representation ability in rate of reaction topic. The test captures four aspects on analytical thinking and four levels of multiple representations (macroscopic, sub-microscopic, symbolic and mathematic). A group of experts confirmed the construct and face validity of the Test of Analytical Thinking based on Multiple Representation (TAT-MR) with 32 items. The TAT-MR was then validated by participating 449 high school students. The test characteristics were analyzed usingRasch model with Partial Credit Model-1 Parameter Logistic (PCM-1PL) approach. The results of theRaschmodeling show that there are 22 TAT-MR items with excellent reliability. Hence, the TAT-MR is acceptable as a good instrument to collect the data. This study suggests that TAT-MR will prove to be a useful instrument for measuring the students’ ability on analytical thinking and chemical representation for rate of reaction topic in chemistry learning.